Mathematical Model, Simulation and Scale up of Batch Reactor Used in Oxidative Desulfurization of Kerosene - Ahmed, Ghazwan Saleh; Humadi, Jasim I.; Aabid, Ahmad A. (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
In this paper, a mathematical model for the oxidative desulfurization of kerosene had been developed. The mathematical model and simulation process is a very important process due to it provides a better understanding of a real process. The mathematical model in this study was based on experimental results which were taken from literature to calculate the optimal kinetic parameters where simulation and optimization were conducted using gPROMS software. The optimal kinetic parameters were Activation energy 18.63958 kJ/mol, Pre-exponential factor  2201.34 (wt)-0.76636. min-1  and the reaction order 1.76636. These optimal kinetic parameters were used to find the optimal reaction conditions which used to obtain a high conversion (≥ 99%). These optimal reaction conditions were reaction temperature 379.4 oK and reaction time 160 min. A scale up to batch reactor was conducted using these optimal kinetic parameters and optimal reaction conditions and the results showed the best reactor size that can be used at a diameter of 1.2 m.